MARITIME ECONOMIC INTEGRATION OF MUARO SAKAI PORT BETWEEN THE DUTCH COLONIAL AND THE INDRAPURA SULTANATE 17-18 AD - Johan Septian Putra (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2022)
This research aims to interpret pattern of integration of economy-maritime in Muaro Sakai Port and describe historical and political-economic link between Indrapura Sultanate and Dutch Company. This research is library research with historical research method, they are: heuristic, verification, synthesis and historiography. Result of the research, prove that Indrapura Sultanate and Dutch Company had integration to raise maritime economy southern coast of Sumatra. They contributed for the trading in regional and international links with other company. Muaro Sakai Port had the biggest role from the transaction of trading such pepper, gold, and other spices to distribute untill foreign out of Sumatra certainly. The conclusion is effect of their cooperation, finally made Indrapura Sultanate reduced its sovereignty in coast of West Sumatra especially in political and economy. But in the other hand, Indrapura Kingdom become one of the success kingdom in Nusantara in international trading